CD5 positive B‐ALL, a uniquely aggressive subcategory of B‐ALL? A case report and brief review of the literature. Issue 1 (30th September 2018) - Staley, Elizabeth M.; Feldman, Alexander Z.; Koenig, Richard G.; Hill, Benjamin
Abstract: CD5 antigen expression in B‐cell acute lymphoblastic leukemia (B‐ALL) is exceptionally rare. There are six detailed case reports in the literature, with only 16 cases described. Case series analyzing the frequency of aberrant B‐ALL immunophenotypes suggest that this variant may occur in as little as 2‐4.5% of all B‐ALL cases, with one series having no CD5 + positive cases. Herein we report a case of CD5 + B‐ALL in a 15‐year‐old female, and review the previously reported cases. As limited information is available, more data from prospective clinical trials are required to determine whether CD5 positivity portends a poorer prognosis.